Module Voltage Balancing Algorithm for Phase Shifted SPWM Controlled Cascaded Multilevel Inverter - Gupta, Suruchi; Deore, SR (International Journal of Computer Sciences and Engineering, 2025)
Multilevel inverters are considered to be an effective and practical solution for increasing power demands and harmonic reduction. They have been attracting attention because of increased power ratings, better harmonic performance and optimized electromagnetic interferences. Among several topologies proposed in literature, Cascaded H-bridge Multilevel Inverter (CMI) stands out due to its advantage in modularization, extendibility and minimization in number of power semiconductors. But one of the major limitations in case of Cascaded Multilevel Inverter is voltage unbalance across dc capacitors with increase in output voltage levels. The module voltage balancing algorithm such as sorting strategy has been proposed for modular multilevel inverter as well as Level Shifted controlled Cascaded Multilevel Inverter in literature. This paper explores basic operating principle of a seven level Cascaded Multilevel Inverter. Carrier based modulation techniques have been summarized. Also, in this paper the sorting strategy for module voltage balance has been proposed for Phase Shifted (PS) SPWM controlled seven level Cascaded Multilevel Inverter. Total Harmonic Distortion (THD) along with module voltage balancing band has also been analyzed.